Common Mistakes

This page contains examples and explanations of common mistakes I see a lot when TAing proof-based classes. They're mainly issues with how the proof is structured rather than the content of the proof itself, so a lot of what's written here also applies to other classes.

Table of Contents

Backward "Proofs"

This one is the easiest to explain. The main thing to keep in mind is that proofs have a direction. When writing a proof, you should pay attention to the direction of the implication symbol "    \implies". If you need to prove the statement "if PP then QQ," then your proof needs to be structured like this:

P        Q.P \implies \cdots \implies Q.

In other words, you assume PP is true and write statements that eventually lead you forward to QQ. I often see students structure their proof as follows:

Q        P,Q \implies \cdots \implies P,

which is true. Thus, if PP then QQ.

When structured this way, you can only prove Q    PQ \implies P, which is the converse of P    QP \implies Q.

Example 1.

Let nNn \in \N. Show that if n2n \geq 2, then n222n^2 - 2 \geq 2.

Backward "proof":

n222n24n2,\begin{aligned} n^2 - 2 &\geq 2 \\ n^2 &\geq 4 \\ n &\geq 2, \end{aligned}

which is true. Therefore n222n^2 - 2 \geq 2 is true.

The "    \implies" symbols aren't written, but they're there. When you write what's above, you're really saying

    n222    n24    n2.\begin{aligned} &\phantom{\implies} n^2 - 2 \geq 2 \\ &\implies n^2 \geq 4 \\ &\implies n \geq 2. \end{aligned}

As mentioned above, this means the "proof" is structured like this:

n222        n2.n^2 - 2 \geq 2 \implies \cdots \implies n \geq 2.

Many times, when you have a backward proof, you can reverse the arrows to turn it into a correct. However, this doesn't always have to happen, so take a minute to think about whether the reverse implication is true.

Solution.

Correct proof: For this problem, reversing the implications fixes the proof. This is because all the statements below are actually equivalent (for positive integers).

    n2    n24    n222.\begin{aligned} &\phantom{\implies} n \geq 2 \\ &\implies n^2 \geq 4 \\ &\implies n^2 - 2 \geq 2. \end{aligned}
Exercise 1.

If we replace nNn \in \N with xRx \in \R in Example 1, the statements are no longer equivalent. Which of the following statements is no longer equivalent to the rest?

  1. x2x \geq 2
  2. x24x^2 \geq 4
  3. x222x^2 - 2 \geq 2

Your answer should be phrased as "statement (i) is no longer equivalent to statement (j)." You should also be able to give a counter-example (i.e., a specific value of xx for which "(i)     \implies (j)" or "(j)     \implies (i)" is false).

Giving Dummy Variables Meaning

This mistake is a much more subtle than what I wrote above, and it's easier to explain with an example. First, let's recall a definition.

Definition

Let f ⁣:ABf\colon A \to B be a function. Then ff is surjective if

bBaA:f(a)=b.\forall b \in B\, \exists a \in A : f\p{a} = b.

Or in words, ff is surjective if for every bBb \in B, there exists aAa \in A such that f(a)=bf\p{a} = b.

In the statement

bBaA:f(a)=b,()\forall b \in B\, \exists a \in A : f\p{a} = b, \tag{$*$}

the variables a,ba, b in (*) are called dummy (or bound) variables. They are called this way because a,ba, b only have meaning within the statement above. This is easier to see once you realize that you can just swap a,ba, b for any symbols you want. For example, the following statements are equivalent to (i.e., have the exact same meaning as) (*).

  1. yBxA:f(x)=y\forall y \in B\, \exists x \in A : f\p{x} = y
  2. BA:f()=\forall \clubsuit \in B\, \exists \spadesuit \in A : f\p{\spadesuit} = \clubsuit
  3. 🤯B🤓A:f(🤓)=🤯\forall 🤯 \in B\, \exists 🤓 \in A : f\p{🤓} = 🤯

Dummy variables are just labels and only make sense in the statement they appear in. However, I see a lot of students reuse the label for a dummy variable in a different statement, which is not correct.

Example 2.

Let f ⁣:ABf \colon A \to B and g ⁣:BCg \colon B \to C be surjective functions. Show that gf ⁣:ACg \circ f \colon A \to C is also surjective.

The mistake I'm talking about usually looks like this:

Wrong "proof":

Since gg is surjective,

cCbB:g(b)=c.(1)\forall c \in C\, \exists b \in B : g\p{b} = c. \tag{1}

Similarly, because ff is surjective,

bBaA:f(a)=b.(2)\forall b \in B\, \exists a \in A : f\p{a} = b. \tag{2}

Thus,

cCaA:g(f(a))=g(b)=c.(3)\forall c \in C\, \exists a \in A : g\p{f\p{a}} = g\p{b} = c. \tag{3}

The issue is that the bb in (1), (2), and (3) are all different. Actually, (3) is not even a proper statement since bb isn't even defined in (3). To drive the message home, remember that we can just relabel dummy variables without changing the meaning, so the above is equivalent to this:

Since gg is surjective,

CB:g()=.(1)\forall \star \in C\, \exists \bigstar \in B : g\p{\bigstar} = \star. \tag{1}

Similarly, because ff is surjective,

BA:f()=.(2)\forall \diamondsuit \in B\, \exists \heartsuit \in A : f\p{\heartsuit} = \diamondsuit. \tag{2}

Thus,

CA:g(f())=g(b)=.(3)\forall \sharp \in C\, \exists \natural \in A : g\p{f\p{\natural}} = g\p{b} = \sharp. \tag{3}

The correct proof looks similar, but the key difference is that it uses the assumptions rather than just restating them. Again, the ideas are correct, but the issue is how the proof is written.

Solution.

Correct proof: Let cCc \in C. Since gg is surjective, there exists bBb \in B such that g(b)=cg\p{b} = c. Similarly, because ff is surjective, there exists aAa \in A such that f(a)=bf\p{a} = b. Thus,

g(f(a))=g(b)=c.g\p{f\p{a}} = g\p{b} = c.

Since cc was arbitrary, we are done.